Non-Clinical Cell Therapy Development Using the NCG Mouse Model as a Test System. (May 2023) - Smutova, Viktorija; Pará, Camila; Foret, Morgan K.; Bennamoune, Nehla; Hung, Selly; Spickler, Catherine; Riffon, Renee; Rowe, Jenny; Festin, Stephen; Authier, Simon
The NCG triple immunodeficient mice on a NOD/Nju background lack functional/mature T, B, and NK cells, and have reduced macrophage and dendritic cell function. This study characterized the NCG mouse model for toxicity, engraftment and tumorigenicity assessments of cell therapies, using CD34 + hHSPC adult mobilized cells with two myeloablation regimens. Mice received sub-lethal irradiation or busulfan and were then injected intravenously with CD34 + hHSPCs (1.0 x 106 cells/mouse) or PBS (control), while positive control animals received 2 x 106 HL-60 cells/mouse. hCD34+ cell donors were treated with the mobilizing agent G-CSF prior to leukapheresis. Following injections, mouse blood samples were collected to assess engraftment rates by flow cytometry with body weights recorded periodically up to 20 weeks post-cell injection. No significant clinical signs or body weight changes were observed. At week 10 post-cell injection, the peripheral blood chimerism of hCD45+ cells was above 20%. While mCD45+ concentration was constant between week 10 and 17 in whole blood samples, hCD45+ concentration and chimerism slightly decreased at week 17. However, chimerism remained above 10%, with busulfan-treated mice presenting higher values. Chimerism was further assessed by quantifying human Alu sequences in blood and multiple organs using qPCR. Alu sequences were most abundant in the spleen and bone marrow, while lowest in the testes. In the positive control group, expected mortalities due to tumorigenesis were observed between days 27 and 40 post-cell injection. Overall, study results may be used to inform study design and potential toxicological endpoints relevant to non-clinical cell therapy development.